Adults with autism spectrum disorder show evidence of figural aftereffects with male and female faces. (October 2015) - Walsh, Jennifer A.; Vida, Mark D.; Morrisey, Marcus Neil; Rutherford, M.D.
Highlights: Adults with autism spectrum disorder (ASD) show significant figural aftereffects. Adults with ASD show somewhat separate aftereffects for male and female faces. Adults with ASD show evidence of typical face adaptation. This study provides further evidence of intact face adaptation in adults with ASD. Abstract: The norm-based coding model of face perception posits that face perception involves an implicit comparison of observed faces to a representation of an average face (prototype) that is shaped by experience. Using some methods, observers with autism spectrum disorder (ASD) have shown atypical face perception, but other methods suggest preserved face perception. Here, we used a figural aftereffects paradigm to test whether adults with ASD showed evidence of norm-based coding of faces, and whether they encode separate prototypes for male and female faces, as typical observers do. Following prolonged exposure to distorted faces that differ from their stored prototype, neurotypical adults show aftereffects: their prototype shifts in the direction of the adapting face. We measured aftereffects following adaptation to one distorted gender. There were no significant group differences in the size or direction of the aftereffects; both groups showed sex-selective aftereffects after adapting to expanded female faces but showed aftereffects for both sexes after adapting to contracted face of either sex, demonstrating that adults with and without ASD show evidence of partially dissociable male and female face prototypes. This is the first study to examine sex-selective prototypes using figural aftereffects in adults with ASD and replicates the findings of previous studies examining aftereffects in adults with ASD. The results contrast with studies reporting diminished adaptation in children with ASD.